2006
DOI: 10.1590/s0100-06832006000300015
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da Gliricidia sepium sobre nutrientes do solo, microclima e produtividade do milho em sistema agroflorestal no Agreste Paraibano

Abstract: RESUMOGliricidia sepium é uma leguminosa arbórea que tem sido utilizada em sistemas em aléias no semi-árido nordestino por apresentar bom desenvolvimento em condições de estresse hídrico. Entretanto, há pouca informação disponível sobre o efeito da introdução dessa espécie nos agroecossistemas da região. No presente estudo, objetivou-se avaliar a influência da distância de plantas de Gliricidia sepium sobre características da cultura do milho e do solo e microclima no Agreste Paraibano. O estudo foi realizado … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 16 publications
(11 reference statements)
0
20
0
17
Order By: Relevance
“…Similarly, some studies reported that a greater tree proximity may reduce (MARIN et al, 2007) corn yield in different rows, while others report no effect (LEITE et al, 2008). It was also observed that proximity effects depend on genotype (LEITE et al, 2008) and environmental factors, including the study year and type of organic fertilizer used (MARIN et al, 2006). Plant height and ear insertion height (Table 2), and some green ear yield traits (marketable green ear weight in 2010, total green ear and marketable green ear weight of both husked and unhusked ears, and the number of marketable husked ears in 2011; Table 3) were significantly greater in left-row plants than in middle-and right-row plants.…”
Section: Alley System (Second Year)mentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, some studies reported that a greater tree proximity may reduce (MARIN et al, 2007) corn yield in different rows, while others report no effect (LEITE et al, 2008). It was also observed that proximity effects depend on genotype (LEITE et al, 2008) and environmental factors, including the study year and type of organic fertilizer used (MARIN et al, 2006). Plant height and ear insertion height (Table 2), and some green ear yield traits (marketable green ear weight in 2010, total green ear and marketable green ear weight of both husked and unhusked ears, and the number of marketable husked ears in 2011; Table 3) were significantly greater in left-row plants than in middle-and right-row plants.…”
Section: Alley System (Second Year)mentioning
confidence: 97%
“…Studies on proximity effects may help farmers determine the number of rows of annual crops that can be grown between the rows of trees to maximize yield. These studies may also be useful in assessing competition between species, the effects of the tree species on soil nutrients and microclimate (MARIN et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Já Young (1988) afirma que uma das principais funções desses sistemas é a conservação do solo, numa abordagem biológica. Marin et al (2006), no agreste paraibano, constataram que embaixo da copa de árvores houve aumento nos teores de P e K extraíveis do solo em até 2,5 mg kg -1 e 214 mg kg -1, respectivamente, comparando-se a um local a 3 m de distância das copas. Já Franco et al (2002), na Zona da Mata de Minas Gerais, comprovaram que a erosão do solo é menor em sistemas agroflorestais do que em sistemas convencionais, chegando a uma redução de 2400 kg ha -1 ano -1 .…”
Section: Sistemas Agroflorestaisunclassified
“…Isto revela a capacidade dos sistemas arborizados em reduzir a ocorrência de eventos extremos de temperatura e com isso melhorar as condições de produção. Marin et al, (2006), no Agreste Paraibano, observaram que num SAF, com linhas da espécie arbórea Gliricidia sepium e cultivo de batata nas entrelinhas, as temperaturas mínimas do ar foram similares nas posições embaixo das árvores e a 3 m de distância; entretanto, as temperaturas máximas no período de estudo foram, em média, 2 °C mais elevadas a 3 m do que embaixo da copa das árvores. Para a temperatura do solo, as mínimas foram similares a 0 e 3 m de distância das árvores; entretanto, as temperaturas máximas do solo foram inferiores sob a espécie arbórea, ao longo das quatro épocas do ano estudadas, apresentando, em geral, valores entre 24 e 31 °C, enquanto a 3 m das árvores as temperaturas máximas no solo oscilaram entre 27 e 41 °C.…”
Section: Temperatura Do Ar E Do Solounclassified